Reliability of Seismic Signal Analysis for Earthquake Epicenter Location Estimation Using 1 Hz GPS Kinematic Solution. (September 2021) - Sha'ameri, A.Z.; Wan Aris, W.A.; Sadiah, S.; Musa, T.A.
Highlights: GPS seismic signal is a time series derived from kinematic coordinate data. Epicenter estimation using surface wave due to the unavailability of surface wave. Time frequency analysis is the best method to measure the parameters. Results are benchmarked with seismometer data with comparable accuracy. Abstract: This paper proposed a reliable analysis method of Global Positioning System (GPS) derived seismic signal to locate the epicenter of a far-field regional earthquake. The surface wave of the seismic signal is utilized due to the attenuation in the body wave which is conventionally used in seismometer. The main contribution is the identification of time-frequency representation (TFR) as a signal analysis method to derive the time of arrival (TOA) for epicenter location estimation using multilateration technique. The comparison was made with other methods such as directly from the time representation, the instantaneous energy, and the power spectrum estimation. The data from the 2004 Sumatra Andaman earthquake captured from four GPS continuously operating reference stations (GPS CORS) were used in the analysis. To validate the accuracy of the proposed method, the estimated epicenter location was compared with the data released by the United States Geological Survey (USGS). The estimated location shows an error of about 0.0572 degrees (6.3 km) in latitude and 0.2848 degrees (31.33 km) in longitude. This is comparable to previous studies using seismometer with an average error of 25 km for far field earthquakes and 20 km for recent work on GPS derived seismic signals for near field earthquakes.